Date seed and date seed oil - Mohd Jaih, Abdul Afiq; Abdul Rahman, Russly; Che Man, Yaakob; Al-Kahtani, Hassan A.; Tengku Mansor, Tengku Salwani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Date palm is an important plant in arid regions with more than 20 varieties reported all over the world. Date seed is a byproduct of date fruit industry which is normally being discarded, used as animal feed ingredient or turned into non-caffeinated coffee by the Arabs. About 11-18% of date fruit weight is the seed which is composed of carbohydrates, dietary fiber, fat, ash and protein. In addition, the antioxidant content in date seed oil (DSO) was found to be comparable with olive oil, which can be as a good source of antioxidant in order to fulfill the consumers demand. Oleic acid is the major fatty acid found in DSO, followed by lauric, linoleic, palmitic and myristic acid. However, different varieties of date fruits have different fatty acid compositions. This paper reviewed the potential use of date seed and date seed oil in order to discover and develop its usage and find out the suitable application of these seed and oil.